Morphological Characterization and Kinship Analysis of the Kepel Plant (Stelechocarpus Burahol) - Mastsani Durrotul Jannah; Umi Barokah (Journal La Lifesci, 2026)
Kepel (Stelechocarpus burahol) is an endemic Javanese plant whose natural populations are declining, requiring conservation based on scientific evidence. This study aimed to characterize the morphological variation and analyze the phenotypic relationships of kepel populations across five ecological zones in Kebumen Regency: West, South, Central, East, and North. A total of 25 individuals were examined using a quantitative descriptive survey. Vegetative traits (leaf length, leaf width, stem diameter) and generative traits (flower diameter) were measured, while environmental parameters were recorded to support data interpretation. Numerical taxonomy analysis was conducted using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) based on standardized Euclidean distances. The results showed substantial morphological variation among zones, with stem diameters ranging from 27.7 to 30.5 cm and leaf lengths from 17.5 to 19.8 cm. Significant correlations were observed between soil pH, humidity, and temperature with key morphological traits (r = 0.70–0.90). The UPGMA dendrogram revealed three major clusters corresponding to distinct microhabitats. These findings indicate local adaptation of kepel populations in Kebumen and provide a scientific basis for both in situ and ex situ conservation of local germplasm.